RsmW, Pseudomonas aeruginosa small non-coding RsmA-binding RNA upregulated in biofilm versus planktonic growth conditions. Issue 1 (December 2016) - Miller, Christine; Romero, Manuel; Karna, S.; Chen, Tsute; Heeb, Stephan; Leung, Kai
Abstract Background Biofilm development, specifically the fundamentally adaptive switch from acute to chronic infection phenotypes, requires global regulators and small non-coding regulatory RNAs (sRNAs). This work utilized RNA-sequencing (RNA-seq) to detect sRNAs differentially expressed inPseudomonas aeruginosa biofilm versus planktonic state. Results A computational algorithm was devised to detect and categorize sRNAs into 5 types: intergenic, intragenic, 5′-UTR, 3′-UTR, and antisense. Here we report a novel RsmY/RsmZ-type sRNA, termed RsmW, inP. aeruginosa up-transcribed in biofilm versus planktonic growth. RNA-Seq, 5'-RACE and Mfold predictions suggest RsmW has a secondary structure with 3 of 7 GGA motifs located on outer stem loops. Northern blot revealed two RsmW binding bands of 400 and 120 bases, suggesting RsmW is derived from the 3'-UTR of the upstream hypothetical gene, PA4570. RsmW expression is elevated in late stationary versus logarithmic growth phase in PB minimal media, at higher temperatures (37 °C versus 28 °C), and in bothgacA andrhlR transposon mutants versus wild-type. RsmW specifically binds to RsmA proteinin vitro and restores biofilm production and reduces swarming in anrsmY/rsmZ double mutant. PA4570 weakly resembles an RsmA/RsmN homolog having 49 % and 51 % similarity, and 16 % and 17 % identity to RsmA and RsmN amino acid sequences, respectively. PA4570 was unable to restore biofilm and swarming phenotypes in ΔrsmA deficient strains. Conclusion Collectively, our study reveals an interesting theme regarding another sRNA regulator of the Rsm system and further unravels the complexities regulating adaptive responses forPseudomonas species.